Tantangan guru sma/ma melakukan implementasi pembelajaran kewirausahan pada masa pandemi covid-19 di jawa timur - Rozakiyah, Desy Santi; Al Siddiq, Imamul Huda; Pratiwi, Seli Septiana (Universitas Dr.Soetomo, 2021)
This study aims to apply the application of enterpreneur learning during the pandemic in senior high school at East Java.Â This research was motivated by aplication of learning during pandemic. The challenge of teachers in implementating entrepreneurship learning in a pandemic was having difficulties applying learning. Cause teachers needed good comunication with students to learning doing independently. This study uses a quantitative approach using a questionnaire distributed to teachers wich teacher entrepreneurship subjects in East Java. In addition, this study also uses a qualitative approach by conducting interviews.the results of this study indicate that problems face to face learning in providing enterpreneur learning were during the pandemic, because of it did not implementation enterpreneur lerning had difficulty in providing practices to students.Keyword : learning in pandemic, implementations enterpreneur learnings activity.